Educational Attainments among Chenchu Tribe: Issues and Challenges - B, Ramesh (Studies in Humanities and Social Sciences (SH&SS), 2024)
Chenchus are one among the Particularly Vulnerable Tribal Groups (PVTGs) Communities of erstwhile Andhra Pradesh, confined to the Nallamalai forest. Haimendorf states that the Chenchus, in their physical make-up, conform largely to a racial Veddoid, a primitive tribe of Sri Lanka. Chenchus are unique in their culture, customs, and identity. Ignoring this fact, the government has treated them on par with other tribal communities and initiated unsuited developmental programs for their upliftment. Their education level has not exceeded 32 percent despite many provisions, recognizing the importance of this often-ignored aspect and the gaps in earlier studies, this study has made a comprehensive attempt to trace the root causes of their low literacy rate. To fulfill the study objectives, extensive and prolonged fieldwork was conducted across selected Ashram schools in Prakasam district of Andhra Pradesh. Deep interactions with primary stakeholders, including students, parents, and teachers, provided the opportunity to examine the root causes of low literacy in detail. Based on the researcher's observations and the perceptions of primary stakeholders, the study suggests some tailor-made recommendations for the improvement of education among the Chenchu tribes.